RELATIONSHIP BETWEEN ORGANIZATION BEHAVIOR AND LEADERSHIP STYLE ON EMPLOYEE WORK DISCIPLINE - Bangun, Rejeki; Simamora, Helprida; Yona, Mira; Tampubolon, Rikson Pandapotan (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
Researching employee work discipline is a very interesting topic because it is one of the factors that influence organizational performance. The purpose of this research is to check and verify how organization behavior and leadership style influence on employee work discipline. SPSS version 25 and a questionnaire for 101 respondents are used in this research. This research uses multiple linear regression techniques along with statistical analysis and quantitative research. Multiple linear regression analysis results for organization behavior (X1) of 6.440 with a significance value of 0.000 and leadership style (X2) of 3.637 with a significance value of 0.000 were produced by researchers based on SPSS data analysis. The results of the simultaneous test (F test) showed a significance value of 0.000 and a score of 43.854. The conclusion of this study, the first hypothesis is that organization behavior has a significant effect on employee work discipline, the second hypothesis is that leadership style has a significant effect on employee work discipline and the last hypothesis is that the two variables (organization behavior and leadership style) have a simultaneous influence on employee work discipline.